2004
DOI: 10.1103/physrevlett.92.255702
|View full text |Cite
|
Sign up to set email alerts
|

Reliable First-Principles Alloy Thermodynamics via Truncated Cluster Expansions

Abstract: In alloys cluster expansions (CE) are increasingly used to combine first-principles electronicstructure calculations and Monte Carlo methods to predict thermodynamic properties. As a basis-set expansion in terms of lattice geometrical clusters and effective cluster interactions, the CE is exact if infinite, but is tractable only if truncated. Yet until now a truncation procedure was not well-defined and did not guarantee a reliable truncated CE. We present an optimal truncation procedure for CE basis sets that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
136
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 33 publications
0
136
0
Order By: Relevance
“…Furthermore, CE is a stringent test case for compressive sensing because a significant amount of effort has been expended developing advanced model building techniques, which have been implemented in sophisticated general-purpose computer codes. [15][16][17][21][22][23][24][25] …”
Section: 20mentioning
confidence: 99%
“…Furthermore, CE is a stringent test case for compressive sensing because a significant amount of effort has been expended developing advanced model building techniques, which have been implemented in sophisticated general-purpose computer codes. [15][16][17][21][22][23][24][25] …”
Section: 20mentioning
confidence: 99%
“…Cluster expansions are, however, known to converge fast, so that the expansion can be truncated at a finite distance and at low orders of many-body patterns. [50][51][52][53] Additionally, the system of equations is likely to contain linear dependencies: for instance, there could exist a configuration whose pattern count is a linear combination of the counts of two other configurations. This may, in principle, be tackled by avoiding superposition of configurations while sampling.…”
Section: The Occurrence Matrix and Its Inversionmentioning
confidence: 99%
“…30 It was found that this constraint significantly improves the quality of the fit. ͑b͒ Single width.…”
Section: A Methods For Generating ␣mentioning
confidence: 99%